An update on current clinical pathogenesis, prevention,and nutritional aspects of nephrolithiasis: a review (Journal of Renal and Hepatic Disorders, 2025)
Nephrolithiasis, commonly known as kidney stone disease, is a prevalent condition characterized by the formation of hard crystalline deposits within the renal system, primarily due to metabolic abnormalities in urinary composition. In India, the prevalence of urinary stone disease is estimated to be around 12%, with a significant proportion at risk of progressing to renal impairment if left untreated. This review explores both pharmacological and nutritional strategies for the prevention and management of recurrent kidney stones. A comprehensive literature search was conducted using databases such as PubMed and Google Scholar, and major publishers including Springer Nature, Bentham Science, Taylor & Francis, and Elsevier. Pharmacological interventions such as thiazide diuretics, indapamide, allopurinol, and potassium citrate have been shown to reduce urinary calcium and uric acid levels, thereby mitigating stone formation. In parallel, several medicinal plants, including Asparagus racemosus, Virataradigana, and Boerhaavia diffusa, exhibit diuretic and antiurolithiatic properties and have shown promising outcomes in traditional medicine and preliminary clinical studies. Although the pharmacological agents demonstrate well-established mechanisms of action and clinical efficacy, the supportive role of herbal remedies offers a complementary pathway, particularly in populations with limited access to conventional therapies. However, the current body of clinical evidence for herbal therapies remains limited in scope and rigor. Thus, while the combined approach of pharmaceutical and plant-based interventions offers a comprehensive strategy for reducing stone recurrence and preserving renal function, further large-scale, randomized clinical trials are necessary to validate these findings and to establish standardized protocols for effective nephrolithiasis management.
Keywords: Renal stones; Calcium oxalate crystals; Urinary stones; Pharmacological treatment; Non-pharmacological treatment; Herbal plants; Clinical trials